Spatial analysis framework for community-based watershed management in tropical uplands of the Philippines - Godilano, Esteban Celeste (Ann Arbor Michigan UMI Company, 1998)
The watershed forms a convenient and logical landscape unit to assess effects of human-induced disturbance on ecological processes, and to formulate community-based management plans to mitigate such disturbances. My research goal is to develop a spatial analysis framework to strengthen the capacities of community stakeholders to evaluate environmental quality, formulate alternative land management strategies, and provide mechanisms to strengthen policies through the application of geographic information and technology. The Matalom River Watershed in Leyte, Philippines served as the study site for my research. The approach was to evaluate watershed-relevant policies, construct a spatial database, survey watershed households, conduct spatial analyses, and involve communities in a case study developing multipurpose cadastral base maps. Policy analysis showed that overlapping policies, foreign interventions, and commercialization of reforestation programs have become the bottleneck to implementation of government natural resource programs. At the village level, results indicate that 40% of the villages are located downstream where soils are acidic, a major constraint to food production. Sixty percent are located upstream on calcareous soils but in an environment that is difficult to access. Upper villages have more biodiversity in terms of perennial food crops and agroforestry species compared to downstream villages. Of the total cultivated area, 49% (2008 ha) are occupied by tenant cultivators, while timberland areas (841 ha) continue to be encroached by the community, and are under intensive resource extraction. This encroachment is contrary to government policies that abolished tenancy 25 years ago. The government continues to establish forest conservation policies to mitigate these resource extraction practices. Conditions adding to the degradation of watershed resources include tenants who, on average, are six years younger than landowners, own two or more farm animals, and have more individuals to feed compared to owner-cultivators. These conditions significantly contribute to intensive land use and abuse. Conversely, owner-cultivators plant a greater number of agroforestry tree species in their homestead. Spatial analysis using geographic information technology identified areas of accelerated land and water resource degradation, determined areas best suited for conservation practices, and implemented "what if" scenarios based on policy guidelines. This analysis provides mechanisms for stakeholders to mitigate the fragile ecosystems in the watershed. The final watershed landscape plan, mapped from a myriad of data sources and constructed using modern GIS technology, has no precedent on this scale for this region of the Philippines. This research contributes to a new science of watershed conservation in the Philippines using tools of many fields of study to find an acceptable balance between resource conservation and utilization.--Abstract.
Thesis (Ph.D.)--Cornell University, 1998.
Keywords: Biology, Ecology -- Philippines; Geography -- Philippines; Agriculture, Soil Science -- Philippines